High-speed surface profilometry based on an adaptive microscope with axial chromatic encoding - Luo, Ding (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2021)
An adaptive microscope with axial chromatic encoding is designed and developed, namely the AdaScope. With the ability to confocally address any locations within the measurement volume, the AdaScope provides the hardware foundation for a cascade measurement strategy to be developed, dramatically accelerating the speed of 3D confocal microscopy.